2007
DOI: 10.1021/ja063857q
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopropyl Conjugation and Ketyl Anions:  When Do Things Begin to Fall Apart?

Abstract: Results pertaining to the electrochemical reduction of 1,2-diacetylcyclopropane (5), 1-acetyl-2-phenylcyclopropane (6), 1-acetyl-2-benzoylcyclopropane (7), and 1,2-dibenzoylcyclopropane (8) are reported. While 6*- exists as a discrete species, the barrier to ring opening is very small (<1 kcal/mol) and the rate constant for ring opening is >10(7) s(-1). For 7 and 8, the additional resonance stabilization afforded by the benzoyl moieties results in significantly lower rate constants for ring opening, on the ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 74 publications
1
28
0
4
Order By: Relevance
“…(1)]. [2][3][4][5] However, examples involving the fragmentation of a spatially separated radical anion yielding a localized radical anion and a neutral molecule are rather unknown [Eq. (2)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1)]. [2][3][4][5] However, examples involving the fragmentation of a spatially separated radical anion yielding a localized radical anion and a neutral molecule are rather unknown [Eq. (2)].…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 summarizes the various thermochemical values for the diphenyl-and di-A C H T U N G T R E N N U N G alkyl-substituted endoperoxides and corresponding reactive intermediates. The overall driving force for the fragmentation of the distonic radical anion DG fragðCORRO À Þ is given by Equation (5).…”
mentioning
confidence: 99%
“…However, a body of work by Tanko and coworkers has provided evidence that this assumption is not necessarily valid. [3][4][5][6] They demonstrated by electrochemically generating a series of cycloalkylketone radical anions that both charge and spin are governing factors in the reactivity of radical-anion rearrangements. The radical anions in these studies were observed to undergo a carbon-carbon bond fragmentation yielding a single species containing a spatially separated radical and anion, which is otherwise known as a distonic radical anion [Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Por muitos anos, assumiu-se que a reatividade dos ânions radicais, em particular seu rearranjo e reações de dissociação eram similares às dos radicais neutros. [284][285][286][287] Contudo, Tanko e colaboradores demonstraram que existem exceções, e que ambos os sítios de carga e spin governam a reatividade dos ânions radicais, principalmente em seus rearranjos. 287 Existe um grande número de artigos científicos envolvendo ânions radicais, cuja clivagem resulta em espécies distônicas.…”
Section: Tabela 32 -Comprimento Das Ligações Em å Para Os âNions Raunclassified
“…[284][285][286][287] Contudo, Tanko e colaboradores demonstraram que existem exceções, e que ambos os sítios de carga e spin governam a reatividade dos ânions radicais, principalmente em seus rearranjos. 287 Existe um grande número de artigos científicos envolvendo ânions radicais, cuja clivagem resulta em espécies distônicas. 200,284,287 Por outro lado, exemplos envolvendo a dissociação de ânions distônicos, cujos produtos da reação sejam um ânion radical e uma molécula neutra ainda são desconhecidos.…”
Section: Tabela 32 -Comprimento Das Ligações Em å Para Os âNions Raunclassified